METHODOLOGICAL ASPECTS OF ASSESSING THE STEEL FRAMES RELIABILITY - Klymenko, Vasyl; Kravchenko, Volodymyr; Zotsenko, Mykola; Vynnykov, Yuriy; Martynenko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2019)
The peculiarities of biogas technology application in the falling leaves utilization plants are analyzed and the application of soil cement is proposed to create the basic elements of such plants. A new schematic and constructive solution of biogas fermenter (bioreactor) with application of soil-cement technology with a blending method for efficient functioning of technological chain of biogas fermentation of fallen leaves and other plant residues for energy supply systems has been developed. The possibility of reliable isolation of the space of the bioreactor to the excavation of the pit from the surrounding array with soil cement screen is substantiated. The corrosion resistance of the soil cement waterproof screen has been proved.